CZECH REPUBLIC UNIVERSITIES SCOUT FOR POSSIBLE COOPERATION WITH USM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 8 March 2016 – Representatives from two Czech Republic universities came for an official visit to Universiti Sains Malaysia (USM) to develop longterm plans for cooperation, especially in the field of Engineering.